Assessment of Educational Protection Tools (APE) of Block in Early Childhood Education - Miftayul Yani, Aziza (PT Inovasi Pratama Internasional, 2026)
This study aims to evaluate the use of Educational Props (APE) blocks in improving the cognitive, motor, and social-emotional development of early childhood. The assessment was conducted through observation, documentation, and interviews with teachers and children in the 4–5 year old age group at an early childhood education institution. The results of the study indicate that the structured use of blocks can improve children's classification, construction, fine motor coordination, and social skills such as cooperation and communication. The obstacles found were the suboptimal variation in block use and the lack of educators' understanding of constructive play-based stimulation strategies. The implications of this study encourage teachers to use a guided play approach to make the use of APE more effective.